Zagreb indices of block-edge transformation graphs and their complements - Bommanahal Basavanagoud; Shreekant Patil (Indonesian Combinatorial Society (InaCombS), 2017)
In this paper, we obtain expressions for first and second Zagreb indices and coindices of block-edge transformation graphs G^ab. Analogous expressions are obtained also for the complements of G^ab.